How do oil prices affect stock market returns in financial sectors：evidence from China and the U.S. - Huang, Chuyao (2018)
This study examines the relationship between changes in oil prices and stock returns (nation stock returns and financial sector stock return), using VAR model and granger causality test. In this study, I consider and select the ag-gregate stock market indices from two countries, China and the US, which reflect and present the most crucial and vital developing and developed fi-nancial markets in the world. Additionally, except the whole stock market, the study also consider correlations from key selected financial sectors. The study collected the daily time series data from Datastream with S&P500 index and Shanghai Composite index as well as their financial sector indexes and the sample period runs from 1st January 1990 to 31st December 2017. Sev-eral key points are highlight as follow: (i) Changes in WTI oil prices have a negative effect on U.S. S&P500 stock return. (ii) WTI oil price changes have no significant relationship with China's Shanghai composite stock price returns. (iii) Changes in WTI oil prices have positive effect on stock returns of financial sector in China. (iv) The negative relationship between WTI oil prices changes and financial sector stock returns in U.S. (v) There is one-way causality from oil price changes to stock return in financial sector both in U.S. and in China. To elucidate this study’s correlations between changes in WTI oil prices and stock returns could be utilized in financial investments and risk hedging.